The Impact of Visual Learning Strategy on the Achievement of Second Intermediate Grade Female Students and their Attitude toward Science Course (Journal of Misan Researches, 2021)
This study aims at finding The Impact of Visual Learning Strategy on the Achievement of Second Intermediate Grade Female Students and their Attitude toward Science Course, the researcher followed the experimental research method, and she chose the research sample from the second intermediate grade students from a school (Umm Waraqah High School for Girls). The sample consisted of (60) female students divided into two equal groups (experimental group and control group). After making the equivalence between the two groups in a number of variables, the research experiment and then its tools (the achievement test and the measure of attitude towards science) were applied, data were collected and statistical treatment was carried out using the (SPSS) program, and the results showed the superiority of the students of the experimental group who studied according to the visual education strategy over the students of the control group who studied  According to the usual method in the achievement test and the measure of direction, so the researcher recommended using the visual education strategy in teaching and including it within the curricula and the teachers’ and teachers’ guide, and holding training courses for the teaching staff to familiarize them with the steps of the visual education strategy, and suggested conducting similar research to know the effect of the visual education strategy in subjects and classes  different and other